Ganda Land, Ganda Labor, and Ganda’s Love: Empire’s Militarized Intimacy of Trans-Pinays - Abad, Nine (The Columbia Journal of Asia, 2025)
This paper investigates how the U.S. military-industrial complex in the Philippines sustains racialized and gendered sexual economies of capitalism that disproportionately exploit poor transgender Filipina women (trans-Pinays). It traces the historical foundations of these dynamics from colonial agricultural dispossession and liberal economic restructuring to contemporary security agreements and military basing. Through the lens of militarized intimacy, U.S. imperialism operates not only through territorial domination but through desires that eroticize and exploit the feminized colonial subject. Trans-Pinays, situated at the margins of legality and visibility, become effective laborers within these economies: desired yet disposable, visible yet unprotected. Understanding these systems of domination is essential to exposing how those systems sustain themselves through intimate acts of dehumanization. This article examines the complex interplay of American imperialism, militarized masculinity, and the commodification of trans-Pinays’ bodies, using the 2014 murder of Jennifer Laude as a critical site of analysis. Jennifer Laude’s murder is not an isolated act of transphobic violence, but rather an imperial crime that renders visible the violence embedded in capitalism.